If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2)(x + 1) = (2x + -5) + 1 Reorder the terms: (-2 + x)(x + 1) = (2x + -5) + 1 Reorder the terms: (-2 + x)(1 + x) = (2x + -5) + 1 Multiply (-2 + x) * (1 + x) (-2(1 + x) + x(1 + x)) = (2x + -5) + 1 ((1 * -2 + x * -2) + x(1 + x)) = (2x + -5) + 1 ((-2 + -2x) + x(1 + x)) = (2x + -5) + 1 (-2 + -2x + (1 * x + x * x)) = (2x + -5) + 1 (-2 + -2x + (1x + x2)) = (2x + -5) + 1 Combine like terms: -2x + 1x = -1x (-2 + -1x + x2) = (2x + -5) + 1 Reorder the terms: -2 + -1x + x2 = (-5 + 2x) + 1 Remove parenthesis around (-5 + 2x) -2 + -1x + x2 = -5 + 2x + 1 Reorder the terms: -2 + -1x + x2 = -5 + 1 + 2x Combine like terms: -5 + 1 = -4 -2 + -1x + x2 = -4 + 2x Solving -2 + -1x + x2 = -4 + 2x Solving for variable 'x'. Reorder the terms: -2 + 4 + -1x + -2x + x2 = -4 + 2x + 4 + -2x Combine like terms: -2 + 4 = 2 2 + -1x + -2x + x2 = -4 + 2x + 4 + -2x Combine like terms: -1x + -2x = -3x 2 + -3x + x2 = -4 + 2x + 4 + -2x Reorder the terms: 2 + -3x + x2 = -4 + 4 + 2x + -2x Combine like terms: -4 + 4 = 0 2 + -3x + x2 = 0 + 2x + -2x 2 + -3x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 2 + -3x + x2 = 0 Factor a trinomial. (1 + -1x)(2 + -1x) = 0Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {1, 2}
| 3[4x+3]=2x-5[3-x]+2 | | a^2-2ax+x^2-9=0 | | -9(-2q-73)-83q=8(-8q+65) | | 2(4x+7)=5x+44 | | 8*x+9=33 | | 10+6x=-6x-50 | | [(2x+5)+3y][(2x+5)-3y]=0 | | 14.5=5n-2 | | 8x+6+2x=12+4x | | 4x-8=8x+7-7x | | 5(-17c+53)=-7(5c-45) | | 120=x | | 121=-8m+7(1-7m) | | -10-1=7x-5-x | | -18.04-4.9v+1.6v=14.7v+4(-18.1v+19.97) | | X(a+3)+y(a+3)=0 | | -3(8-11j)=-5(12-6j) | | -3=3x-6x+18 | | 4y-8x=10 | | 55x-11y=253 | | -3(8-11j)=-5(12-j) | | -5d+19-4d=-6(4d+19)-4d | | 8x-15-4x=13 | | 15x+(15)=6 | | 5(-6n+3)=165 | | -4(-18+6n)=-6(13n+15) | | 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 | | 5(-6+3)=165 | | y=3sinx+-4 |